Evaluation of Using Natural Fillers to Improve Moisture Damage Resistance and the Use of Pull-Off Tensile Test in Determining Moisture Damage Resistance in Asphalt Mixture - Kroekphon Rachabut; Preeda Chaturabong (My University, 2020)
Moisture is one of the critical failures affecting asphalt pavement. It has been recently found that moisture created by rainwater and undrained water deteriorate the bonding interface between asphalt mastic and aggregate. Using different mineral fillers can lead to different moisture resistance in the same mix design. Nowadays, waste natural materials allow agriculturists to receive more income by recycling in many industries. In this study, the researchers adopted bagasse and coconut peat grinding into very fine particle passing through the sieve number 200 (0.075 mm) to replace the mineral fillers. Although the indirect tensile strength (ITS) test is commonly used for evaluating the moisture damage resistance of hot-mix asphalt (HMA) in a laboratory, there are some shortcomings in using this test, such as costly, heavy and indirect equipment. Another potential test that is likely to be more advantageous than the ITS test for evaluating the moisture damage resistance is the pull-off tensile strength (POTS) test. However, it is typically measured on a concrete surface, and no results using an asphalt mixture have been reported. The objectives in this study were to investigate the effects of waste natural fillers in asphalt mixture on adhesive bonding caused by moisture, and to determine whether the POTS test is a potential method in measuring moisture damage resistance in a laboratory. Results showed that the tensile strength ratios (TSR) of asphalt mixture with bagasse and coconut peat fillers are approximately equivalent to those with mineral fillers. Results also showed that asphalt mixtures with bagasse and coconut peat fillers can effectively prevent the moisture damage resistance. In addition, with the preliminary result, it was found that the POTS test showed a very good R square (R2) for a relation of TSR with the ITS test. As a result, the POTS can be a valid tool of quantifying moisture damage resistance with better simulating to field behavior, lower cost of equipment, and light weight.
Keywords: Bagasse; Asphalt pavement; Asphalt Pavement Performance Evaluation